2007
DOI: 10.1016/j.laa.2007.05.038
|View full text |Cite
|
Sign up to set email alerts
|

A note on spaces of symmetric matrices

Abstract: We calculate the maximal dimension of linear spaces of symmetric and hermitian matrices with given high rank generalizing a well-known result of Adams et al. AMS (MOS) Subject Classification: 15A30 (55N15).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…5 Moreover, if V contains the scalars, then V is invertible if and only if V is polynomially closed [13]. Besides this, we do not have a good understanding of the structure of invertible matrix subspaces as a subset of Gr k (C n×n ).…”
Section: Theorem 33 ([13])mentioning
confidence: 97%
See 1 more Smart Citation
“…5 Moreover, if V contains the scalars, then V is invertible if and only if V is polynomially closed [13]. Besides this, we do not have a good understanding of the structure of invertible matrix subspaces as a subset of Gr k (C n×n ).…”
Section: Theorem 33 ([13])mentioning
confidence: 97%
“…Otherwise, V is called singular if it does not contain invertible elements. (For singular matrix subspaces, see [5] and references therein.) For a nonsingular matrix subspace V , set Inv(V ) = {V −1 : V ∈ V ∩ GL(n, C)}, where GL(n, C) denotes the group of invertible n-by-n complex entried matrices.…”
Section: Introductionmentioning
confidence: 99%
“…For the (restricted) instanton of charge 2 we can say a little more. The m-effective pair associated to E is in this case (4,6). In the recent work [1] it is shown that the only possibilities for such a pair are to be associated TOME 65 (2015), FASCICULE 5 to either a quotient of…”
Section: Remark 24 -If Cokermentioning
confidence: 99%
“…Notre résultat étend des travaux antérieurs sur le cas c 1 3. happened for example in [14,16,15,3]. On the other side, linear systems have been proved useful in approaching some classical problems in geometry: examples of this phenomenon are, among many others, [4,10,5]. The main connection between the two areas comes from interpreting such a linear system as a vector bundles map, whose kernel and cokernel are again vector bundles on some projective variety.…”
mentioning
confidence: 99%
“…( 6 ) Otherwise a matrix subspace is called singular. (Such subspaces are also of interest [10], [8].) If there exists an invertible element in a subspace V of C n×n over C (or R), then the set of invertible elements is a dense and open subset of V [21, Theorem 2.2].…”
Section: Matrix Subspaces Possessing Invertible Elementsmentioning
confidence: 99%